Comparison of high and low molar activity TSPO tracer [18F]F-DPA in a mouse model of Alzheimer's disease. Issue 5 (May 2020) - Keller, Thomas; López-Picón, Francisco R; Krzyczmonik, Anna; Forsback, Sarita; Takkinen, Jatta S; Rajander, Johan; Teperi, Simo; Dollé, Frédéric; Rinne, Juha O; Haaparanta-Solin, Merja; Solin, Olof
[ 18 F]F-DPA, a novel translocator protein 18 kDa (TSPO)-specific radioligand for imaging neuroinflammation, has to date been synthesized with low to moderate molar activities (Am 's). In certain cases, low Am can skew the estimation of specific binding. The high proportion of the non-radioactive component can reduce the apparent-specific binding by competitively binding to receptors. We developed a nucleophilic synthesis of [ 18 F]F-DPA resulting in high Am (990 ± 150 GBq/µmol) and performed in vivo comparison with low Am (9.0 ± 2.9 GBq/µmol) [ 18 F]F-DPA in the same APP/PS1-21 and wild-type mice (injected masses: 0.34 ± 0.13 µg/kg and 38 ± 15 µg/kg, respectively). The high level of microgliosis in the APP/PS1-21 mouse model enables good differentiation between diseased and healthy animals and serves better to distinguish the effect of differing Am on specific binding. The differing injected masses affect the washout profile and shape of the time–activity curves. Ratios of standardized uptake values obtained with high and low Am [ 18 F]F-DPA demonstrate that there is a 1.5-fold higher uptake of radioactivity in the brains of APP/PS1-21 animals when imaging is carried out with high Am [ 18 F]F-DPA. The differences between APP/PS1-21 and wild-type animals showed higher significance when high Am was used.